Algorithmic power in autocratic regimes: Critical analysis for democratic resilience in the digital age - Paskarina, Caroline (Research Journal in Advanced Humanities, 2026)
This article examines the influence of algorithms in the context of digital authoritarianism and their impact on democratic resilience. Drawing on a synthesis of literature, this work addresses political algorithmics, artificial surveillance technologies, and information control through digital gatekeeping. The article highlights the logic of power algorithms as a form of predictive power relations that obscure and automate control. Case studies from Southeast Asian countries, such as Vietnam, Thailand, and Indonesia, illustrate how autocratic governments use algorithms to filter public sentiment, suppress dissent, and control narratives. The analysis reveals three components of algorithmic politics: predictive and personalized automation, repressive algorithms, and manipulation of information systems. These components demonstrate the extent to which algorithmic power reinforces authoritarian rule while simultaneously eroding the foundation of democratic resilience by dismantling the public sphere of reasoned debate, deepening societal divisions, and diminishing the level of critical citizenship and digital civic engagement. The article urgently proposes rethinking the political theory of power to incorporate technological, epistemological, and emotional frameworks in the digital age.